CALCULATION OF CHARACTERISTICS OF INTERNAL PRESSURE EMISSIONS IN MAIN GAS PIPELINES - Lena Shatakishvili; Dimitri Namgaladze; Tornike Kiziria; Tamaz Ghvanidze (World Science, 2021)
Management of technological operations during the discharge and filling of gas compressor stations and the linear part of the main gas pipelines, start-ups and shutdowns of gas-pumping units and other technological switches, aimed at avoiding exceeding the limit values ​​of the amplitude of gas oscillations in order to increase the operability of the gas transmission system. Main gas pipelines are designed to ensure safe operation during normal working process. The internal pressure as well as its test pressure are safe and will not cause bursting of the gas pipeline. But often during the operation of the main gas pipeline, there are on-off procedures and various fluctuations. Therefore, due to these processes and cyclic loading, fatigue of the pipeline metal takes place. It is also known from practice that during normal operation, pipeline destruction may occur. Therefore, it is important to determine the value of dynamic pressure emissions, for a high level, which is very important. It was found that the series of internal pressure obeys the Rayleigh distribution law. On the basis of this law, an analytical dependence of the amount of internal pressure emissions for a given level was obtained, according to which numerical results were obtained.